CITRA PENYULUHAN PERTANIAN DAN ADOPSI INOVASI DALAM MENINGKATKAN PRODUKTIVITAS PETANI - Johand David Wetik (Jurnal Kommunity Online, 2020)
AbstractIncreasingly agricultural extension image is one of the goals of agricultural extension systems Indonesia. This research aims to obtain a description of the image of agricultural extension and adoption of innovation in enhancing the capacity of farmers and the productivity of farmers in the Sipayung village, Cipanas Sub District, Lebak District of in Banten province. This research is a quantitative research, and survey methodes. The research samples are 100 respondents from a population of 309 farmers rice field.Data processing by path analysis. The results showed the image of agricultural extension have a relationship and a direct influence in enhancing the capacity of farmers as well as directly and indirectly in improving the productivity of farmers. The image of an average extension in the high category on the attributes, utility, culture, personality and relationships. Adoption of innovation has a direct relationship and influence in increasing the capacity of the farmers but has no direct influence in increasing the productivity of farmers. Average adoption of innovation in the category of high benefit, can be tried and can be observed. Simultaneously the image of agricultural extension and adoption of innovation and the related effect on increasing the capacity of farmers and farmer capacity-related and affect the productivity of farmers. In improving the productivity of farmers must be continued to maintain the image of the agricultural extension. The strengthening the capacity of farmers is the one strategy to increase the productivity of farmers.Keywords: Image of agricultural extension; the adoption of innovations; the productivity of farmersAbstrakPeningkatan citra penyuluhan pertanian merupakan salah satu tujuan dari sistem penyuluhan pertanian Indonesia. Penelitian ini bertujuan untuk menganalisis pengaruh citra penyuluhan pertanian dan adopsi inovasi terhadap kapasitas petani serta produktivitas petani  di Desa Sipayung Kecamatan Cipanas Kabupaten Lebak Provinsi Banten.Jenis penelitian ini adalah pendekatan kuantitatif dengan metodesurvei. Sampel penelitian ini berjumlah 100 responden dari populasi309 petani padi sawah. Pengolahan data dengan analisis jalur. Hasil penelitian menunjukan citra penyuluhan pertanian mempunyai pengaruh secara langsung dalam meningkatkan kapasitas petani serta secara langsung dan tidak langsung dalam meningkatkan produktivitas petani. Citra penyuluhan rata-rata dalam kategori tinggi pada atribut, kemanfaatan, budaya, kepribadian dan relasi.Adopsi inovasi mempunyai pengaruh secara langsung dalam meningkatkan kapasitas petani namun tidak berpengaruh secara langsung dalam meningkatkan produktivitas petani. Adopsi inovasi rata-rata dalam katagori tinggi pada memberikan keuntungan, dapat dicoba dan dapat diamati.Secara simultan citra penyuluhan pertanian dan adopsi inovasi berpengaruh terhadap peningkatan kapasitas petani. Produktivitas petani dipengaruhisecara tidak langsung oleh citra penyuluhan dan adopsi inovasi melalui kapasitas petani. Dalam meningkatkan produktivitas petani tetap terus menjaga citra penyuluhan pertanian, serta penguatan kapasitas petani senantiasa dilakukan untuk meningkatkan produktivitas petani.Kata kunci: Citra penyuluhan pertanian; adopsi inovasi; produktivitas petani